The Influence of Service Quality Towards Syariah Bank Customer Satisfaction in The New Normal Era - Handaru Indrian S Adi; Hendra Suwardana (INNOVATION RESEARCH JOURNAL, 2021)
This study aims to measure and determine whether customer satisfaction at BRI Syariah Unit Tuban has a significant effect on service quality variables (reliability, physical evidence, confidence, empathy, and responsiveness) in the new normal Covid 19 pandemic era, and to measure and determine the effect of satisfaction. customers at BRI Syariah Unit Tuban simultaneously to the variables of reliability, physical evidence, confidence, empathy, and responsiveness in the new normal covid pandemic era 19.Based on the results of statistical tests it is known that the variable reliability, physical evidence variable, belief variable, empathy variable, and responsiveness variable have a partial and significant influence on customer satisfaction in BRI Syariah unit Tuban in the new normal pandemic covid era 19. Variablesreliability, physical evidence, confidence, empathy, and responsiveness simultaneously have an influence on customer satisfaction with a value of Fcount 210,268> Ftable 2,333, it can be concluded that reliability, physical evidence, confidence, empathy, and responsiveness simultaneously have an influence on customer satisfaction. Syriah Tuban unit in the new normal Covid pandemic era 19.